2014
DOI: 10.1158/1078-0432.ccr-14-1677
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Genotype Is an Independent Prognostic Factor in Primary Gastrointestinal Stromal Tumors of Gastric Origin: A European Multicenter Analysis Based on ConticaGIST

Abstract: Purpose: Although the mutational status in gastrointestinal stromal tumors (GIST) can predict the response to treatment with tyrosine kinase inhibitors, the role of tumor genotype as a prognostic factor remains controversial. The ConticaGIST study sought to determine the pathologic and molecular factors associated with disease-free survival (DFS) in patients with operable, imatinib-naive GIST.Experimental Design: Clinicopathologic and molecular data from 1,056 patients with localized GIST who underwent surgery… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
2
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 34 publications
7
118
2
11
Order By: Relevance
“…While there is some correlation between gastric location, larger size and the presence of mutation 557-558 showing a lower RFS, the predominantly high risk nature of our cohort meant that a majority of operable/operated patients were candidates for adjuvant IM, thereby shifting the onus of this analysis to evaluation of performance of the exon 11 cohort on IM. While Contica GIST study (15) showed poorer outcome of gastric GIST patients with mutation 557-558, our study showed trend towards poorer outcome in that group irrespective of location.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…While there is some correlation between gastric location, larger size and the presence of mutation 557-558 showing a lower RFS, the predominantly high risk nature of our cohort meant that a majority of operable/operated patients were candidates for adjuvant IM, thereby shifting the onus of this analysis to evaluation of performance of the exon 11 cohort on IM. While Contica GIST study (15) showed poorer outcome of gastric GIST patients with mutation 557-558, our study showed trend towards poorer outcome in that group irrespective of location.…”
Section: Discussioncontrasting
confidence: 55%
“…The knowledge of KIT exon 11 mutants having a longer PFS on standard IM and KIT exon 9 mutants potentially benefitting from 800 mg doses of IM has emerged in the advanced setting (19). The Contica GIST study (15), clearly showed that gastric GIST with a KIT del 557-558 had an inferior disease free survival compared to other mutants. A larger study, comprising 11 population based series (n=3,067; mutation analysis-1505), but untreated with IM, concluded that patients with PDGFRA mutations and those with KIT exon 11 duplication/single codon deletion mutations have a favorable recurrence free survival (RFS) with surgery alone (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[10][11][12][13] Several tumor cell-intrinsic molecular prognosticators have been suggested, mainly based on proteins [47][48][49][50][51] or gene signatures 52,53 related to cell proliferation. Potential immune prognostic/predictive parameters have been more recently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Изучение прогностической роли мутаций проводится до начала таргетной терапии, либо как ре-троспективное, либо при изучении контрольных групп пациентов, получавших плацебо [73]. У паци-ентов с мутациями PDGFRA выживаемость выше, чем у пациентов с мутациями KIT [1,49,50,74,75]. Точечные мутации и дупликации в 11-м экзоне KIT коррелируют с менее агрессивным поведением ГИ-СО, так же как и опухоли с мутацими PDGFRA.…”
Section: рис 3 частота мутаций Kit и Pdgfra в 1351 гисо [69]unclassified